2008
DOI: 10.1002/lsm.20659
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of acneiform scarring with CO2ablative fractional resurfacing

Abstract: Successfully combining ablative technology with FP, AFR treatments constitute a safe and effective treatment modality for acneiform scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
248
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(265 citation statements)
references
References 14 publications
12
248
0
5
Order By: Relevance
“…In the present study, it was found that three sessions of ablative fractional CO 2 laser showed significant qualitative and quantitative improvement of atrophic acne scars, which was consistent with previous reports of Chapas et al [32] , Manuskiatti et al [33] and Cho et al [34] . However, Azzam et al reported that patients with boxcar scars showed no improvement using (15 mJ) power by fractional CO 2 laser with appearance of pixilated pattern and acne activation in some cases [24] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, it was found that three sessions of ablative fractional CO 2 laser showed significant qualitative and quantitative improvement of atrophic acne scars, which was consistent with previous reports of Chapas et al [32] , Manuskiatti et al [33] and Cho et al [34] . However, Azzam et al reported that patients with boxcar scars showed no improvement using (15 mJ) power by fractional CO 2 laser with appearance of pixilated pattern and acne activation in some cases [24] .…”
Section: Discussionsupporting
confidence: 93%
“…Previous histologic and immunohistologic studies demonstrated a large difference in results between fat grafting and fractional ablative CO 2 laser for the treatment of acne scars, and favored fat grafting [35] . Histologic and immunohistologic experimental study compared biopsies taken from nude mice before and after fat graft, and showed an increased density of extracellular matrix surrounding the fatty tissue and between the fatty tissue and the dermis [32] . In another study on mice, skin changes with fat grafting were investigated in skin biopsies eight weeks after the graft, which revealed that fat graft caused increased collagen fibers neosynthesis at the recipient site and thickened the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional ablative procedures are available with carbon dioxide laser (CO 2 laser, 10,600 nm) and erbium YAG laser (Er:YAG laser, 2,940 nm) [3][4][5]. The concept of AFR has so far been used for dermal remodeling in the treatment of photodamaged facial skin, rhytides, acneiform scarring, and burn scar remodeling [3,[6][7][8][9][10]. Theoretically, AFR may also facilitate penetration and distribution of topically applied drugs, since the ablated laser holes extend into dermis, thereby possibly acting as channels for drug uptake.…”
Section: Introductionmentioning
confidence: 99%
“…These abrade the surface and help tighten the collagen fibers beneath (5) . All ablative lasers showed high risk of complications (5) , the high risk of complications following traditional CO 2 resurfacing has warranted the development of new treatment modalities (4,15) . This modality was the fractional photo thermolysis (16,17) .…”
Section: Introductionmentioning
confidence: 99%